1990
DOI: 10.3109/07357909009012053
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Validity of the Serum Tumor Marker Phosphohexose Isomerase (PHI) in Patients with Gastrointestinal, Kidney, and Breast Cancer

Abstract: The diagnostic validity of the glycolytic enzyme phosphohexose isomerase (PHI) as a serum tumor marker was evaluated. For this purpose the sensitivity of PHI was determined in 435 patients with histopathologically defined, malignant gastrointestinal, kidney, and mammary tumors prior to primary treatment. To assess the specificity, PHI serum activities were measured in 181 patients with benign diseases and disorders from an internal practice. In gastrointestinal and kidney cancer, PHI reached an overall diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 14 publications
0
47
1
1
Order By: Relevance
“…Autocrine motility factor receptor is overexpressed in various metastatic tumors and is correlated with a poor prognosis (Hirono et al, 1996). The presence of GPI in serum and urine is associated with cancer progression and indicates poor prognosis (Baumann and Brand, 1988;Baumann et al, 1990;Filella et al, 1991). The expression of PGI is stimulated by hypoxia (Yoon et al, 2001;Niizeki et al, 2002).…”
Section: Glucose-6-phosphate Isomerasementioning
confidence: 99%
“…Autocrine motility factor receptor is overexpressed in various metastatic tumors and is correlated with a poor prognosis (Hirono et al, 1996). The presence of GPI in serum and urine is associated with cancer progression and indicates poor prognosis (Baumann and Brand, 1988;Baumann et al, 1990;Filella et al, 1991). The expression of PGI is stimulated by hypoxia (Yoon et al, 2001;Niizeki et al, 2002).…”
Section: Glucose-6-phosphate Isomerasementioning
confidence: 99%
“…Secreted AMF promotes cancer cell invasion and metastasis by stimulating cell motility via an autocrine manner after binding to its 78 kDa seven-transmembrane glycoprotein receptor, gp78/AMFR (13). AMF in the serum or urine can be a tumor marker predicting patients' prognosis with cancer (14)(15)(16). The signaling pathways downstream of AMFR include protein kinase CK2 (17), Rho family regulators, the rho GDP dissociation inhibitor h, and kinesin motor 3A, and is implicated in epithelial-mesenchymal transition by down-regulation of Ecadherin expression through the up-regulation of its transcription suppressor (e.g., Snail; refs.…”
Section: Introductionmentioning
confidence: 99%
“…5 AMF/PHI has also been found to be identical to neuroleukin (NLK), 6,7 a neurotrophic growth factor that supports the survival of spinal and sensory neurons, 8 and maturation factor (MF) mediating the differentiation of human myeloid leukemic HL-60 cells to terminal monocytic cells, 9 suggesting that this cytokine is multifunctional, probably dependent on the target cells. AMF/PHI activities have shown to be elevated in the serum or urine of patients with disseminated malignant tumors such as gastrointestinal, kidney, breast, colorectal, and lung carcinomas, 10,11 , thereby being useful as a tumor-dissemination marker. An immunohistochemical study has demonstrated that the prognosis of AMF/PHI-positive patients with pulmonary adenocarcinoma is poorer than that of negative patients.…”
mentioning
confidence: 99%